Ambient Stable Zwitterionic Perylene Bisimide‐Centered Radical. (12th November 2014) - Schmidt, David; Bialas, David; Würthner, Frank
Abstract: The unexpected introduction of a cationic imidazolium substituent in the 2‐position of a tetrachloro‐substituted perylene‐3, 4:9, 10‐tetracarboxylic acid bisimide (PBI) by the reaction of PBI‐Cl4 1 with the N‐heterocyclic carbene 1, 3‐di‐iso‐propyl‐imidazolin‐2‐ylidene ( i Pr2 Im2 ) enables the isolation of an ambient stable zwitterionic radical. The remarkable stability of this unprecedented PBI‐centered radical facilitates the complete characterization by several spectroscopic methods as well as single crystal structure analysis. Redox studies revealed that i Pr2 Im‐PBI‐Cl4 4 can be transferred reversibly to the corresponding anion and cation, respectively, even on a preparative scale.